Rocks and Hard Places: Gender, Satire, and Social Reproduction in Pre-Revolutionary Iran. Issue 1 (June 2021) - Razavi, Sahar
Abstract: This article examines the ways that Iranian women have been situated in the nation-building exercise from the White Revolution of 1963 to the 1979 revolution and period of consolidation of clerical power. Social Reproduction Theory elucidates critical facets of both state control and spaces of counterhegemonic resistance. These spaces include publications like Tawfiq, a political satire magazine published in the Pahlavi era, which is featured in the analysis as a site of political contestation that could be utilized and expanded by other opposition groups. This paper argues that in contrast to the popularly accepted dichotomy between liberalized and regressive gender roles, this arena represented a critical failure on the part of the secular opposition, which enabled the clerical faction to co-opt and take control of narratives in which they cast themselves as protectors of women and other vulnerable groups.